Infraestrutura de informação: um mapeamento sistemático da literatura - Farias, Tatielly Dias de (2020)
Studies on information infrastructures (II) have gained space in everyday applications due to the massive amount of data from several geographically distributed areas that are shared among themselves, in order to support systems of an organization in which research on II provide a basis for using your concepts in applications. Objectives: From this context, this research aimed to present the most relevant works found in the literature on II as a way to understand this area of study and its fields of application. Methods: The research method adopted for a systematic mapping study, followed by a protocol as a guide to answer the five research questions as a way of extracting and synthesizing primary studies relevant to the topic. Results: 369 relevant relevant primary studies were identified that contributed to the development of the information infrastructure divided by II components, with 15 studies on II standardization, 6 on standard flexibility, 11 with II architecture, 20 on II, 3 on the tensions found in IIs and 8 studies dealing with the evolution of IIs. It was observed that most studies are applications that use II concepts in their formation. This research provides a catalog of information on the studies selected from the application of the included criteria for inclusion or exclusion and which are included as research questions. Conclusion: This research showed that the interest on the information infrastructure has grown over the years with three evidences that some of the studies that have applications reveal concepts as a result of its conception. Therefore, the catalog generated from the results obtained with studies that bring concepts and applications is an important resource to guide and serve as a starting point for future research and improvement of information infrastructures.